Motor and extramotor neurodegeneration in amyotrophic lateral sclerosis: A 3T high angular resolution diffusion imaging (HARDI) study. Issue 7 (December 2013) - Trojsi, Francesca; Corbo, Daniele; Caiazzo, Giuseppina; Piccirillo, Giovanni; Monsurrò, Maria Rosaria; Cirillo, Sossio; Esposito, Fabrizio; Tedeschi, Gioacchino
Abstract: In amyotrophic lateral sclerosis (ALS), diffusion weighted magnetic resonance imaging (DW-MRI) has produced mounting evidence of a widespread white matter (WM) damage within motor and extramotor pathways. To provide novel information about the degenerative process in ALS, overcoming some of the limitations imposed by diffusion tensor imaging (DTI), we performed a high angular resolution diffusion imaging (HARDI) analysis of DW-MRI data. Generalized fractional anisotropy (GFA) was evaluated in 19 patients with ALS and 19 matched control subjects, and was correlated with clinical scores of disability, pyramidal impairment by upper motor neuron (UMN) score and frontal dysfunction by the Frontal Systems Behaviour (FrSBe) scale. Results demonstrated that ALS patients showed a significant decrease of GFA in the WM tracts underneath the left and right precentral gyri and the body of the corpus callosum ( p < 0.05, corrected), where GFA was significantly related to UMN scores ( p < 0.001, uncorrected); and in the left superior longitudinal fasciculus ( p < 0.05, corrected), where GFA was significantly related to FrSBe scale scores ( p < 0.01, uncorrected). In conclusion, this study revealed a pattern of motor and extramotor frontal diffusivity abnormalities (probably related to behavioural and cognitive dysfunctions) showing a spatial distribution similar to what was previously described in ALS − frontotemporal dementia continuum.